2019
DOI: 10.2503/hortj.utd-r002
|View full text |Cite
|
Sign up to set email alerts
|

A Project to Reconstruct a Food Production Area Following the Adverse Impacts of the Great East Japan Earthquake and Tsunami of 2011: Open Field Vegetables

Abstract: Among large-scale research projects for reconstruction of agriculture and fisheries of the area damaged by the Great East Japan Earthquake and Tsunami (2011), the results of field trials and research concerning field vegetables including cabbage and broccoli were reviewed. In Miyagi Prefecture, to reconstruct the agriculture of the Sendai Plain coastal area, a mechanized and labor-saving culture system of field vegetables, that can coexist with paddy rice production as the primary source, was chosen. In this a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
0
0
Order By: Relevance
“…As results, they did not focus to manage their farms, but to rebuild and reconstruct their houses. Significant and critical efforts need to be taken to address the adverse impacts and bring the agricultural production into normal such as those reported by Japanese researchers to address the adverse impacts of big earthquake in Japan in 2011 [14][15][16]. The findings on the impacts COVID-19 pandemic found in this study are also consistent with the findings reported by other researchers on the impacts of COVID-19 on agriculture [17][18][19][20][21][22][23][24][25][26][27].…”
Section: Discussionsupporting
confidence: 86%
“…As results, they did not focus to manage their farms, but to rebuild and reconstruct their houses. Significant and critical efforts need to be taken to address the adverse impacts and bring the agricultural production into normal such as those reported by Japanese researchers to address the adverse impacts of big earthquake in Japan in 2011 [14][15][16]. The findings on the impacts COVID-19 pandemic found in this study are also consistent with the findings reported by other researchers on the impacts of COVID-19 on agriculture [17][18][19][20][21][22][23][24][25][26][27].…”
Section: Discussionsupporting
confidence: 86%
“…The cultivated area per operator was more than 8000 m 2 for those using natural light, while those using artificial light used less than 5000 m 2 . Considering the damage done to the soils of Miyagi Prefecture by the tsunami [68,69], the soilless nature of VF makes it highly suitable for agriculture in damaged areas. The uptake of VF has been supported by government subsidies, creating employment opportunities and helping with regional development [70,71].…”
Section: Distribution Of Vertical Farming In Miyagi Prefecturementioning
confidence: 99%